Women's Participation in Mining Rejection Movement in Tumpangpitu Mountain (An Analysis of Ecofeminism) - Saputra, Rico Amdan; Handayani, Baiq Lily (Laboratorium Sosiologi FISIP Universitas Jember, 2018)
The main objective of this research is to analyze the participation of women in the rejection movement of gold mines in Mount Tumpangpitu in Sumberagung Village, Pesanggaran - Banyuwangi. By using qualitative descriptive methods, data are collected through interviews, direct observation, and literature study. The theory used for the analysis is Ecofeminism Vandana Shiva. The researcher is also participatory in the rejection action. The results showed that women were involved in this environmental movement of their own volition. Most of the women who participated in the campaign had a low level of education. Their involvement is based on concerns over the loss of their family's source of income and life. They worry that the ecosystem will be damaged, and they will have difficulty finding resources for them to survive. Keywords: Women's participation, Ecofeminism, Mount Tumpangpitu, Gold mining Referensi: Candraningrum, D. (2013). Ekofeminisme I : Dalam tafsir Agama,Pendidikan, Ekonomi dan Budaya. Yogyakarta: Jalasutra. Candraningrum, D. (2014). Ekofeminisme II :Narasi Iman,Mitos,Air dan Tanah. Yogyakarta: jalasutra. ———————–. (2015). Ekofeminisme III :Tambang, Perubahan Iklim,Air dan Memori Rahim. Yogyakarta: jalasutra. Denzin, Norman K. dan Yvonna S. Lincoln (eds.). 2009. Handbook of Qualitative Research. Terj. Dariyatno dkk. Jogjakarta: Pustaka Pelajar. Kartika, T. (2014). Perempuan Lokal vs Tambang Pasir Besi Global. Jakarta: Yayasan Pustaka Obor Indonesia. Miles, B. Mathew dan Michael Huberman. 1992. Analisis Data Kualitatif Buku Sumber Tentang Metode-metode Baru. Jakarta: UIP. Mitchell, Bruce. Setiawan, B. Rahmi, DH. 2000. Pengelolaan Sumberdaya Alam Lingkungan. Penerbit Gajahmada University Press. Yogyakarta. Pranoto, N. (2017). Ekofeminisme : Kritik Sastra Berwawasan Ekologis dan Feminis. Yogyakarta: Cantrik Pustaka . Shiva, V and Mies, M. 2005. Ekoveminisme Perspektif Gerakan Perempuan Dan Lingkungan .Yogyakarta: IRE Pres Shiva, Vandana, 1988, Bebas Dari Pembangunan; Perempuan, Ekologi, dan Perjuangan hidup di India, Jakarta: yayasan Obor Indnesia. Shiva, Vandana, 2002, Water and Wars: Privatization, Pollutionand Provid, Yogyakarta: Insist Press. Susilo, R. K. (2009). Sosiologi Lingkungan. Jakarta: Rajawali Pers. Sumaryadi, I. N. (2005). Efektifitas Implementasi Kebijakan Otonom Daerah. Jakarta: Citra Utama. Thong, R. P. (1998). Feminist Thought pengantar paling komprehensif kepada aliran utama pemikiran feminis. Yogyakarta: Jalasutra. Skripsi : Sutomo, B. (2014).’Eksploitasi Alam Di Gunung Tumpangpitu Dalam Perspektif Ekologi. Marx. Jember: Universitas Jember Jurnal: Yuni, D.A. (2013). Konflik Pertambangan Emas Di Gunung Tumpangpitu Desa Sumberagung Kecamatan Pesanggaran, 5. Jember: Universitas Jember Internet: Detik.com/berita/182807/benjolan-pada-warga-buyat-bukan-karena-pencemaran.[Di akses pada 5 April 2018] Mongabay.co.id-tambang-emas-tumpang-pitu-dari-masa-ke-masa-bagian tambang-emas-tumpang-pitu-dari-masa-ke-masa-bagian. [Diakses 25 mei 2017]. Kompas.com/read/2016/08/20/12135481/pulau.merah.banjir.lumpur.perusahaan.tambang.emas.diminta.segera.penuhi.amdal. [Diakses pada 21 oktober 2017]. Tribunnews.com-ratusan-warga-menolak-pertambangan-tumpang-pitu-supaya-dihentikan. [Diakses pada tanggal 22 mei 2017]. Rapper.com-warga-bersama-ibu-ibu-menolak-tambang-emas-tumpang-pitu. [Diakses pada tanggal 22 mei 2017]. Mongabay.co.id-nasib-warga-kala-melawan-pemasangan-kabel-listrik-tambang-emas-tumpang-pitu/ .[Diakses pada tanggal 18 oktober 2017].